Good faith exempt from guilt: utopia of the opponents before the decisions of the Superior Court of the District of Cúcuta - Civil Chamber Specialized in Land Restitution - Cristian Antonio Bohórquez Galviz (Postulados: Revista Sociojurídica)
This article about the land restitution processes in Colombia established in Law 1148 of 2011, shows us where these processes come f rom, which are considered as reparation measures for the victims of the armed conflict, their two procedural stages are established: administrative and judicial. , as well as resources and mechanisms used by the opponents who are the current owners of the properties in dispute and who within a period of 15 days make the response opposing claims for recognition and end with the parameters to configure the objective elements of the good guilt-f ree faith in the rulings issued by the Superior Court of the Judicial District, Civil Chamber Specialized in Restitution of lands of the city of Cúcuta in the purchase of rural properties in the department of Cesar, is a documentary investigation with interpretive technique, own analysis the social sciences, where the legal hermeneutic methodology was applied with the legal review of jurisprudence to resolve the problem question and thus be able to establish the conclusion on good faith exempt f rom fault as a utopia of the opponents of jurisprudential decisions in specialized chambers of restitution of lands in Norte de Santander.